Plan estratégico de marketing para la empresa productora y comercializadora de tilapia “Rana Bonita” del cantón Zamora, provincia de Zamora Chinchipe - Armijos Gonzalez, Melania (2014)
This study was conducted in order to propose a Strategic Marketing Plan for Company Producer and marketer of Tilapia "Rana Bonita" Zamora Canton province of Zamora Chinchipe. The population surveyed were registered customers to December 2013 in manufacturer and marketer of tilapia "Rana Bonita", the same as it was 1,250 client included in the population of the canton Zamora, the sample is applied to 303 surveys to customers and the company. The survey results are presented in statistical tables. From the results of the investigation can be determined that 15% of staff working within the company "Rana Bonita" city of Zamora, has not received any training course, 85% said that the company does not have any advertising, the manager said that the company does not offer any promotion for its customers. The producer and marketer of tilapia "Rana Bonita" company was established in 1993 as an initiative of the owner's engineer Costa Ramos Muñoz, the same does not have a marketing plan that allows positioning in the local market. Thus it can be concluded: In the analysis of the current situation of the company or analysis of internal strengths has 13 factors and 6 weaknesses, the strengths outweigh the weaknesses. The evaluation of internal factors a rating of 3.07, higher than the 2.00 average determined indicating that the company has a balanced performance between:strengths and weaknesses. The analysis and assessment of external to the company "Rana Bonita" factors, we get the macro environment, and define the opportunities and threats it faces daily, this evaluation has a rating of 3.21, higher than the average rating, indicating that the company properly seize opportunities. We propose a strategy to properly take advantage of opportunities using the strengths, ie the 13 strengths as summarized in the SWOT analysis, you can make good use of one or more external conditions favorable opportunities; It also suggests a strategy by which the strengths used to deal with the threats of the macro environment, defined below, four strategies to exploit opportunities and minimize weaknesses; and a strategy to address the threats, manage to overcome the negative conditions or weaknesses of the company. For the fulfillment of the strategic marketing plan of the company "Rana Bonita" a reference budget proposes $ 11,940.00, the same shall not affect the cash flow of a single economic period, but will be spending on investments to be made in different years of compliance, strategic marketing plan. The company "Rana Bonita" should be used properly, its strategic location in the Amazon area where the conditions for aquaculture production, as water production without which it is impossible to possess. Develop and implement the strategic marketing plan for a five-year horizon, which is clearly stated strategic objectives, the strategies to follow, goals, policies to follow.